Optimized Protocol for Characterization of Mouse Gut Innate Lymphoid Cells - Valle-Noguera, Ana; Gómez-Sánchez, María José; Girard-Madoux, Mathilde J. H.; Cruz-Adalia, Aranzazu (Frontiers in Immunology, 2020)
Since their discovery, innate lymphoid cells (ILCs) have gradually been gaining greater relevance in the field of immunology due to their multiple functions in the innate immune response. They can mainly be found in mucosal and barrier organs like skin, gut and lungs and have been classified into five main types (NKs, ILC1s, ILC2s, ILC3s and Lti cells) according to their function and development. They all play major roles in functions such as tissue homeostasis, early pathogen defense, regulation of inflammation, or tissue remodeling. ILCs are mostly tissue-resident cells tightly bound to the tissue structure, a fact that requires long and complex protocols that do not always provide sufficient yield for analysis. This suggests the need for optimized approaches aimed at ensuring that enriched and viable ILC samples are obtained, in order to furnish quality results. Herein a detailed protocol is established for obtaining a single-cell suspension highly enriched in lymphoid cells from mouse gut in order to identify the different subsets of ILCs by means of flow cytometry. The cell marker panel and flow cytometry gating strategies for identification and quantification of all the different ILC populations are provided for simultaneous analysis. Moreover, the protocol described includes a procedure for studying the different cytokines produced by ILC3s involved in maintaining the integrity of the gut barrier and defending against extracellular pathogens. As a result, herein an efficient method is presented for studying mouse ILCs within the lamina propria of the small intestine and colon; this can constitute a useful tool for future investigations in the field.